(untitled) (Scientific journal of the Fergana State University, 2024)
This article focuses on the problems of students of the Faculty of Natural Sciences to formulate the linguodidactic concept of teaching English. It cites solutions to be found on this issue, with examples of a number of proposals. At the same time, the opinions of a number of researchers are studied.